A Study on characteristics improvement of concentrated flux IPM BLDC motor using the flared-shape rotor Structure with Ferrite Magnets - Young Yoon, Keun (International Journal of Engineering and Technology, 2018)
Background/Objectives: This paper proposes the alternative possibilities that the flared-shape rotor structure of IPM BLDC motor has the similar high performances as the basic IPM BLDC motor that has the spoke structure with ferrite magnet.Methods/Statistical analysis: The proposed rotor structure has the structural feature of ferrite magnets which has inserted as the flared shape in the rotor core. Through the finite element analysis, the performances of the proposed flared-shape IPM BLDC motor has compared with the basic spoke type IPM BLDC motor.Findings: This paper show the comparison with the analysis results of 2D FEM and it has shown that the proposed IPM motor has a substitute for the spoke type IPM motor which requires low cost and high output power. Especially the proposed flared IPM motor has a low pulsation of torque than the basic type IPM motor. So the proposed flared IPM motor has the advantage for acoustic noise and vibration the spoke type IPM motor.Improvements/Applications: The proposed flared-shape IPM BLDC motor is suitable for as electric vehicle and home appliances motor.Â Â